Com quem podemos contar? Autoridade, Empoderamento e Responsabilização em Moçambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (Portuguese Translation of IDS Working Paper 546, Maputo: Instituto de Estudos Sociais e Económicos, 2021)
Neste artigo, usamos 'diários de governação' para analisar as interações entre pessoas pobres e autoridades em contextos de Fragilidade, Conflitos e Violência (FCVAS) em Moçambique. Questionamos os significados de empoderamento e responsabilização, sob ponto de vista de pessoas pobres e marginalizadas, e procuramos perceber como essas pessoas vêem as instituições que as governam, incluindo as que as providenciam bens e serviços básicos, entre os quais os de saúde e segurança. As conclusões mostram que, mesmo que as percepções e, com elas, os conceitos de empoderamento e responsabilização que emergiram, não difiram significativamente dos identificados na literatura, em termos de ação e mobilização há diferenças. Constatamos que, nos nossos locais de pesquisa, as pessoas raramente se mobilizam, mesmo com a má prestação de serviços básicos e a prevalência de injustiças. Muitos consideram-se 'incapazes' de influenciar ou forçar as 'autoridades' a responderem às suas preocupações e demandas. Por 'Autoridade Pública' entendem qualquer entidade ou pessoa capaz de resolver os problemas da comunidade, enquanto Estado, geralmente reconhecido como 'Autoridade', é percebido como indistinto do Partido Frelimo e do Governo, mas também é visto como um pai, embora ausente, e aquele que se esquece e abandona os seus filhos.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

Who Can We Count On? Authority, Empowerment and Accountability in Mozambique - Chaimite, Egidio; Forquilha, Salvador; Shankland, Alex (IDS Working Paper 546, Brighton: Institute of Development Studies, 2021)
In this paper, we explore the use of a governance diaries methodology to investigate poor households’ interactions with authority in fragile, conflict and violence-affected settings in Mozambique. The research questioned the meanings of empowerment and accountability from the point of view of poor and marginalised people, with the aim of understanding what both mean for them, and how that changes over time, based on their experiences with governance. The study also sought to record how poor and marginalised households view the multiple institutions that govern their lives; providing basic public goods and services, including health and security; and, in return, raise revenues to fund these services. The findings show that, even if the perceptions and, with them, the concepts of empowerment and accountability that emerged do not differ significantly from those identified in the literature, in terms of action and mobilisation there are distinctions. In our research sites we found that people rarely mobilise, even faced with prevalent injustices and poor basic service provision. Many claim to be ‘unable’ to influence or force ‘authorities’ to respond to their concerns and demands.
Accepted: 2021-02-02T10:30:54Z
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; access to services / acesso a serviços; accountability / responsabilização; authority / autoridade; conflict / conflito; empowerment / empoderamento; fragility / fragilidade; governance / governação; health / saúde; institutions / instituições; justice / justiça; mobilization / mobilização; security / segurança; taxation / tributação

‘We all have the same right to have health services’: a case study of Namati’s legal empowerment program in Mozambique - Schaaf, Marta; Falcao, Joana; Feinglass, Ellie; Kitchell, Erin; Gomes, Nadja; Freedman, Lynn (BMC Public Health, 2020)
Background: Legal empowerment and social accountability are two strategies that are increasingly used to address gaps in healthcare in low- and middle-income countries, including failure to provide services that should be available and poor clinical and interpersonal quality of care. This paper is an explanatory case study of a legal empowerment effort that employs community paralegals and trains Village Health Committees (VHCs) in Mozambique. The research objective was to explore how community paralegals solved cases, the impact paralegals had on health services, and how their work affected the relationship between the community and the health sector at the local level. Methods: The case study had two components: (1) a retrospective review of 24 cases of patient/community grievances about the health system, and (2) qualitative investigation of the program and program context. The case reviews were accomplished by conducting structured in-depth interviews (IDIs) with those directly involved in the case. The qualitative investigation entailed semi-structured Key Informant Interviews (KIIs) with district, provincial, and national health managers and Namati staff. In addition, focus group discussions (FGDs) were held with Health Advocates and VHC members. Results: Case resolution conferred a sense of empowerment to clients, brought immediate, concrete improvements in health service quality at the health facilities concerned, and seemingly instigated a virtuous circle of rightsclaiming. The program also engendered incipient improvements in relations between clients and the health system. We identified three key mechanisms underlying case resolution, including: bolstered administrative capacity within the health sector, reduced transaction and political costs for health providers, and provider fear of administrative sanction. Conclusions: This study contributes to the limited literature regarding the mechanisms of legal empowerment case resolution in health systems and the impact of hybrid legal empowerment and social accountability approaches. Future research might assess the sustainability of case resolution; how governance at central, provincial, and district level is affected by similar programs; and to what extent the mix of different cases addressed by legal empowerment influences the success of the program.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; access to services / acesso a serviços; accountability / responsabilização; empowerment / empoderamento; health / saúde